Transition clinics in pediatric rheumatology in Colombia: reflection on a necessary shortcomings - Lauren Natalia Ramirez; María Elisa Hoyos; Angela Catalina Mosquera-Pongutá; Gerardo Quintana-López (Advances in Rheumatology)
Abstract Introduction Transition clinics are conceived as programs dedicated to the active, multidimensional development of a process that addresses the medical, psychosocial, educational, and vocational needs of pediatric patients suffering from a chronic disease that will persist into adulthood. Their understanding is justified in physiological, psychological, and sociocultural terms on the basis of the differential morbidity and mortality associated with a chronic disease that begins in childhood and prevails into adulthood. Materials and methods Here, we reflect on the history, structure, and impact of transition clinics in pediatrics, with an emphasis on pediatric rheumatologic diseases. Additionally, we propose comprehensive reflection as an alternative for the patient, their family, and the medical team, outlining guidelines for development, implementation, and evaluation. Results The transition of care should commence in early adolescence, considering each patient’s cognitive ability as a condition for the initiation of an educational process involving introspection into the disease. Interdisciplinarity is defined as a team that addresses the clinical, physical, emotional, and social dimensions of each patient and their interaction with the environment within the framework of individualized care and family support. Despite this, the lack of evidence supporting standardized guidelines for the implementation and overall effectiveness evaluation of these interventions was highlighted. Conclusions The transition process is considered successful when the patient is adherent and has a positive and informed perception of their health‒disease journey. We urge the generation of evidence documenting the comprehensiveness of processes inherent to transition clinics as the foundation of necessity.